The Involvement of Insulin-Like Growth Factor 2 Messenger Ribonucleic Acid-Binding Protein 2 in the Regulation of the Expression of Breast Cancer-Related Genes - Gao C; Li L; Jin X; Song X; Li H; Xu X; Dong C; Ma B (Breast Cancer: Targets and Therapy, 2022)
Chao Gao,1 Li Li,2 Xixin Jin,1 Xinyu Song,1 Huiling Li,1 Xiaoli Xu,1 Chao Dong,1 Binlin Ma1 1State Key Laboratory of Pathogenes, Prevention and Treatment of High Incidence Diseases in Central Asia, Department of Breast and Thyroid Surgery, Affiliated Cancer Hospital of Xinjiang Medical University, Urumqi, People’s Republic of China; 2State Key Laboratory of Pathogenes, Prevention and Treatment of High Incidence Diseases in Central Asia, Department of Gynecology and surgery, Affiliated Cancer Hospital of Xinjiang Medical University, Urumqi, People’s Republic of ChinaCorrespondence: Chao Dong; Binlin Ma, State Key Laboratory of Pathogenes, Prevention and Treatment of High Incidence Diseases in Central Asia, Department of Breast and Thyroid Surgery, Affiliated Cancer Hospital of Xinjiang Medical University, No. 789 of East Suzhou Street, Urumqi, 830000, People’s Republic of China, Tel +860991-7968088, Fax +860991-7968111, Email dc_dongchao@outlook.com; mabinlinmbl@21cn.comAim: This study investigated the role and mechanism of insulin-like growth factor 2-IGF2BP2 in breast cancer.Methods: IGF2BP2 is overexpressed in MDA-MB-231 human breast cancer cells. Thus, RNA sequencing was used to analyze the differentially expressed genes, Cell Counting Kit-8 was used to detect cell proliferation, and a Transwell assay was used to assess cell invasion. Following on from the RNA sequencing results, Interferon-induced protein with tetratricopeptide repeats 2 (IFIT2), chemokine C-C motif ligand 20 (CCL20), chemokine C-C motif ligand 5 (CCL5), and chemokine C-X-C motif ligand 10 (CXCL10) regulated by IGF2BP2 were subjected to real-time reverse transcriptase-polymerase chain reaction verification.Results: After IGF2BP2 overexpression, 67 genes were up-regulated, and 87 genes were down-regulated. The gene with the most significant up-regulation was homeobox protein 1 (PROX1), and the gene with the most significant down-regulation was Acidic β-crystallin 4 (CRYBA4). The most enriched gene ontology (GO) terms of up-regulated differentially expressed genes are protein binding and cell membrane and of down-regulated differentially expressed genes they are ion binding, cytoplasm, and response to virus. Kyoto Encyclopedia of Genes and Genomes analysis showed that the up-regulated differential genes were mainly enriched in protein processing, the endoplasmic reticulum, and the regulation of actin cytoskeleton, while down-regulated differential genes were mainly enriched in rheumatoid arthritis, chemokine signaling pathways, toll-like receptor signaling pathways, tumor necrosis factor signaling pathways, cytokine-cytokine receptor interaction, and Notch signaling pathways. IGF2BP2 overexpression significantly promoted the proliferation and invasion of breast cancer cells (P < 0.01). Compared with the control group, the IGF2BP2 overexpression group had significantly increased expressions of IFIT2, CCL20, and CXCL10 (P < 0.05).Conclusion: IGF2BP2 may promote the invasion and proliferation of human breast cancer cells by up-regulating breast cancer-related genes, such as IFIT2, CCL20, and CXCL10.Keywords: breast cancer, RNA-binding protein, IGF2BP2, bioinformatics